PENGGUNAAN TELEPON GENGGAM PADA MASYARAKAT PERBATASAN (SURVEI PADA KECAMATAN TANJUNG BERINGIN, KABUPATEN SERDANG BEDAGAI, PROVINSI SUMATERA UTARA) - Meilinia Diakonia Ginting (Jurnal Penelitian Komunikasi dan Pembangunan, 2019)
This study aimed to investigate mobile phone use in the border area in Tanjung Beringin Subdistrict, Serdang Bedagai Regency. This research used quantitative approach. The data were collected from survey. The sample size of 100 people  was determined using the Taro Yamane formula. The number of samples in each village was determined proportionally. The data were analysed using SPSS. It was found that the people predominantly used mobile phones as communication devices, thai is, to make a call and send short messages services. Smartphones providing various attractive services through available applications have also been used by a small number of respondents, mainly to access social networks sites, browse information, and play games both online and offline.